KEPEMIMPINAN KOLABORATIF KEPALA SEKOLAH DAN GURU DALAM PEMBINAAN KARAKTER PESERTA DIDIK DI SMP AL-MA’RUFIYAH TEMPURAN MAGELANG - Novi Andriani; Maryono; Fadhillah Izzatun Nisa; Nur Faozan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is a crucial component in shaping students’ personalities, particularly at the junior secondary school level. Effective character development requires school leadership that is not individualistic but collaborative between principals and teachers. This study aims to analyze the collaborative leadership of principals and teachers in fostering students’ character development at SMP Al-Ma’rufiyah Tempuran Magelang. This research employed a qualitative approach with a case study design. The research subjects consisted of the principal, teachers, and students selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, and analyzed using an interactive data analysis model involving data reduction, data display, and conclusion drawing, supported by triangulation to ensure data validity. The results indicate that collaborative leadership is reflected in the active involvement of principals and teachers in planning, implementing, and evaluating character education programs. The principal acts as a facilitator, policy leader, and role model, while teachers integrate character values into learning activities, habituation programs, and extracurricular activities. Collaborative leadership contributes positively to strengthening school culture, enhancing teacher professionalism, and improving students’ discipline, responsibility, and cooperation. This study concludes that collaborative leadership is an effective approach to character education in junior secondary schools. Keywords: Teacher, Principal, Collaborative Leadership, Character Education, Middle School.